Трям! Здравствуйте! - Козлов Сергей Григорьевич (Наши любимые мультфильмы, 2007)
То же, 2006 Экземпляры: ф.7 (2008) / Инвентарный номер: 43030 / Цена: / Сис.шифр: 84 (2Рос=Рус)6 / Авт.знак: К 59 / ГРНТИ: 17 / ББК: 84 (2Рос=Рус)6